Regulation of Covernotes by Notaries, Land Deed Making Officials (PPAT) Against Parties in Bank Credit Agreements - Sofyan, Ananda Magvirah; Bima, Muhammad Rinaldy; Lestari, Sri (ADVANCED PRIVATE LEGAL INSIGHTS, 2025)
This study aims to analyze the legal consequences of the issuance of Covernote by Notary / PPAT on the parties to a banking credit agreement, identify potential legal problems due to delays or discrepancies in the documents promised in Covernote, and provide an understanding of the role and limitations of Covernote in banking practice as a supporting document for credit guarantees. The method used in this research is empirical juridical with a qualitative descriptive approach, where data is obtained through interviews with Notary / PPAT, banks, and debtors related to the issuance of Covernote, as well as through document studies and relevant laws and regulations. The results show that Covernote does not have binding legal force as a credit guarantee, but is often a reference in the process of disbursing funds by banks. The legal consequences can be in the form of default risk for the debtor if the documents promised in the Covernote cannot be fulfilled, as well as the potential legal responsibility for Notary / PPAT if there is negligence in its issuance. The implications of this research emphasize the need for caution in the issuance of Covernote so as not to cause legal problems for the parties. In addition, banks as creditors need to understand the limitations of Covernote in guaranteeing legal certainty over mortgage rights. The recommendations of this research emphasize the need for clearer regulations related to the issuance of Covernote by Notary/PPAT in order to provide legal protection for all parties involved in banking credit agreements.